Police Description In The Investigation of Criminal Narcotics (study at the north Sumatera National Narcotics Agency) - Agung Anugrah Lubis; Syafruddin Kalo; Madiasa Ablisar; Sunarmi Sunarmi (LEGAL BRIEF, 2020)
Discretion is interpreted as “freedom and/or authority in making decisions to take actions that are considered appropriate or in accordance with the situations and conditions faced wisely and with due regard to all possible considerations and options. This research is a type of empirical normative legal research and the nature of the research used is descriptive-analytical. The data used are primary data and secondary data. The discretion of the police against narcotics crime at the investigation level is regulated in Article 18 paragraph (1) and Article 16 paragraph (1) letter 1 and paragraph (2) of the Police Law. The discretionary power of the police cannot be separated from several factors, namely internal and external factors. The legal consequences of discretionary actions by investigators of narcotics crimes are resolved through general courts.